Determinants and effects of moth population dynamics in altitudinal gradients in northern Fennoscandia - Schott, Tino (University of Tromsø, 2013)
The papers of this thesis are not available in Munin: 1. Schott T., Hagen S.B., Ims R.A. & Yoccoz N.G.: 'Are population outbreaks in sub-arctic geometrids terminated by larval parasitoids?', Journal of Animal Ecology (2010), vol.79:701-708. Available at http://dx.doi.org/10.1111/j.1365-2656.2010.01673.x 2. Schott T., Kapari L., Hagen S.B., Vindstad O.P.L., Jepsen J.U. & Ims R.A.: 'Predator release from invertebrate generalists does not explain geometrid moth outbreaks at high altitudes', The Canadian Entomologist (2013), vol.145:184-192. Available at http://dx.doi.org/10.4039/tce.2012.109 3. Schott T., Ims R.A., Hagen S.B. & Yoccoz N.G.: 'Sources of variation in larval parasitism of two symmetrically outbreaking birch forest defoliators', Ecological Entomology (2012), vol. 37:471-479. Available at http://dx.doi.org/10.1111/j.1365-2311.2012.01386.x 4. Schott T., Svavarsdottir S., Hagen S.B., Kapari L., Vindstad O.P.L., Biuw M., Jepsen J.U. & Ims R.A.: 'Coping with variation in prey abundance and phenology: Comparative breeding performance of two passerines at the northern limit of their geographic range' (manuscript). The aim of this PhD-project has been to increase our knowledge of trophic interactions along altitudinal gradients in a system of sympatric, cyclically outbreaking geometrid moth species in sub-arctic, coastal birch forest in northern Norway. The project resulted in four scientific publications; two sub-studies focused on the causal effect of natural enemies on the observed complex spatio-temporal dynamics of the moth species (Papers 1 & 2). The other two sub-studies investigated the ecological effects of variable moth larvae densities as a resource for predators in the sub-Arctic ecosystem (Papers 3 & 4). In paper 1, we rejected the hypothesis that larval parasitoids might terminate moth population peaks, one of the most important hypotheses on insect population regulation. We, however, found that larval parasitoids can influence local spatial variation in moth population ...